GENOTYPIC SELECTION ON RED CHILI PLANTS RESISTANT TO ANTHRACNOSE DISEASE AT M2 GENERATION - Sa'diyah, Nyimas; Adawiah, Adawiah; Prasojo, Ibnu; Rugayah, Rugayah; Ratih Dirmawati, Suskandini (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2018)
Genotypic selection on red chili palnts resistant to anthracnose disease at m2 generation. A superior anthracnose resistant cultivar was sought to overcome the low production due to anthracnose in red chili. For the development of superior cultivars, it was necessary to select genotypes that were resistant to anthracnose. Selection effectiveness was determined by wide diversity and high reliability. The purpose of this study was to see the diversity and heritability of agronomic characters and resistance to anthracnose on chili plants, and to select genotypes that were resistant to anthracnose. This research was conducted with a design without repetition. The plant material used was the seed of the results of gamma ray mutations in generation M2. The results of this study were: the broad diversity of phenotypes found in all characters observed, while all characters of the genotype observed had broad criteria except plant height at flowering and harvest, and at seedling period. The genotype that should be planted in the next generation was genotype number 136. Genotype number 136 was very resistant to anthracnose infection.